Pharmacologic modeling of primary mitochondrial respiratory chain dysfunction in zebrafish. (July 2018) - Byrnes, James; Ganetzky, Rebecca; Lightfoot, Richard; Tzeng, Michael; Nakamaru-Ogiso, Eiko; Seiler, Christoph; Falk, Marni J.
Abstract: Mitochondrial respiratory chain (RC) disease is a heterogeneous and highly morbid group of energy deficiency disorders for which no proven effective therapies exist. Robust vertebrate animal models of primary RC dysfunction are needed to explore the effects of variation in RC disease subtypes, tissue-specific manifestations, and major pathogenic factors contributing to each disorder, as well as their pre-clinical response to therapeutic candidates. We have developed a series of zebrafish ( Danio rerio ) models that inhibit, to variable degrees, distinct aspects of RC function, and enable quantification of animal development, survival, behaviors, and organ-level treatment effects as well as effects on mitochondrial biochemistry and physiology. Here, we characterize four pharmacologic inhibitor models of mitochondrial RC dysfunction in early larval zebrafish, including rotenone (complex I inhibitor), azide (complex IV inhibitor), oligomycin (complex V inhibitor), and chloramphenicol (mitochondrial translation inhibitor that leads to multiple RC complex dysfunction). A range of concentrations and exposure times of each RC inhibitor were systematically evaluated on early larval development, animal survival, integrated behaviors (touch and startle responses), organ physiology (brain death, neurologic tone, heart rate), and fluorescence-based analyses of mitochondrial physiology in zebrafish skeletal muscle. Pharmacologic RC inhibitor effects were validated by spectrophotometric analysis of Complex I, II and IV enzyme activities, or relative quantitation of ATP levels in larvae. Outcomes were prioritized that utilize in vivo animal imaging and quantitative behavioral assessments, as may optimally inform the translational potential of pre-clinical drug screens for future clinical study in human mitochondrial disease subjects. The RC complex inhibitors each delayed early embryo development, with short-term exposures of these three agents or chloramphenicol from 5 to 7 days post fertilization also causing reduced larval survival and organ-specific defects ranging from brain death, behavioral and neurologic alterations, reduced mitochondrial membrane potential in skeletal muscle (rotenone), and/or cardiac edema with visible blood pooling (oligomycin). Remarkably, we demonstrate that treating animals with probucol, a nutrient-sensing signaling network modulating drug that has been shown to yield therapeutic effects in a range of other RC disease cellular and animal models, both prevented acute rotenone-induced brain death in zebrafish larvae, and significantly rescued early embryo developmental delay from either rotenone or oligomycin exposure. Overall, these zebrafish pharmacologic RC function inhibition models offer a unique opportunity to gain novel insights into diverse developmental, survival, organ-level, and behavioral defects of varying severity, as well as their individual response to candidate therapies, in a highly tractable and cost-effective vertebrate animal model system. Highlights: Rotenone causes delayed development, mitochondrial dysfunction & brain death in larvae. Probucol treatment prevents acute rotenone-induced brain death in zebrafish larvae. Azide causes dose/time-dependent delay, brain death, & behavioral changes in larvae. Oligomycin causes dose/time dependent delay, death, behavioral changes & cardiac edema. Chloramphenicol causes decreased zebrafish survival, brain death, & behavioral changes.